Losing Mood(s): Examining Jihadi Supporters’ Responses to ISIS’ Territorial Decline - Massé, Léa Eveline Jeanne Stéphanie (Terrorism and political violence, 2022)
The fall of the Islamic State in Iraq and Syria (ISIS) has raised a number of questions over the future of the organization and the potential threat it might continue to pose. While some commenters argue that the demise of the Caliphate will reduce ISIS’s global appeal, others have stressed the role that jihadi supporters may play in perpetuating ISIS’s ideological legacy. Yet, little is known on how supporters have responded to recent changes in circumstances. Employing a cognitive dissonance approach, this contribution examines the implications of ISIS’s defeat on twelve jihadi supporters’ commitment. It shows that while a minority of supporters have disengaged, the majority have remained committed to the group. While these differences stress the influence of personal situational factors on supporters’ responses, the data at the same time indicates that dissonance has preceded in some cases ISIS’s defeat. The contribution overall shows that integrating cognitive dissonance theory to the study of radicalization and terrorism can provide a more nuanced understanding of how individuals renegotiate the nature of their involvement in extremism when confronted by changes in circumstances.